Thermal And Optical Performance Of Ingaalp-Based Low- And Gan-Based High-Power Light-Emitting Diode Packages - Abdullah Raypah, Muna Ezzi (2020)
This study was divided into three main parts. In the first part, the performance of indium gallium aluminum phosphide (InGaAlP) low-power (LP) SMD LED affixed to substrates with different configurations. In the second part, the heat-dissipation factor, optical power, luminous flux, and spectral flux of LP LEDs were estimated by extending the application of the equations that were employed for high-power (HP) LEDs. In the third part, the performance of thin film gallium nitride (ThinGaN) HP LED attached to a SinkPAD via solder was evaluated.